Feminist narratives in Indian digital television: A discourse analysis of Scoop - Verma, Amit; Kusmayadi, Ika Merdekawati; Arbani, Mochamad (ProTVF, 2025)
Background: The portrayal of women in media often perpetuates gender disparities, limiting their participation and the impact of their issues. This study addresses the gap in understanding how journalism practices, particularly in India, navigate these challenges, using the web series Scoop as a lens to explore feminist realities within the media industry. Purpose: This study aims to dive into how the Scoop series displays women and feminist ideas through the lens of the feminist theories of Laura Mulvey. Methods: This study employs a qualitative discourse analysis approach and looks closely at the narrative, character development, and cinematic écriture of the series. Results: It reveals that the series has a different point of view from traditional stereotypes; Jagruthi Pathak, as the female lead, is portrayed as a versatile and strong character facing challenges in a male-dominated journalism world. It also exposes how journalism commonly feminizes labor, emphasizing the mix of gender, power, and professionalism. Conclusion: This study concludes by noting that Scoop has pushed feminist stories in Indian media, providing us with a leveled look at females in journalism while handling deep-rooted gender biases. This study also accentuates how essential comprehensive storytelling is for promoting gender equality and its challenge in patriarchal norms. It also makes room for more diversification and allows media representation. Implications: This research advocates for more women to participate in media production and storytelling, stressing needing narratives that shake up societal norms and inspire real change.